KDM2B regulates stroke injury by modulating OGT-mediated 0-GlcNAcylation of SLC7A11 - Yi Li; Liangbo Niu; Dai Zheng; Xinxing Zhang; Lu Feng; Jing Fu (Communications Biology)
Abstract Ischemic stroke poses a significant global health risk. Currently, recanalization of blood flow through surgery or medication is the only effective means to control ischemia-reperfusion injury. This study aims to explore the role and molecular mechanism of OGT in regulating neuronal injury and motor deficits following a stroke. The MCAO and OGD/R models were established to validate the therapeutic efficacy of OGT in mitigating neuronal injury and motor dysfunction following stroke. Molecular biological techniques were employed to assess ferroptosis levels, OGT ubiquitination, and SLC7A11 O-GlcNAcylation. OGT has a therapeutic effect on motor deficits and neuronal damage after stroke by regulating SLC7A11 O-GlcNacylation-mediated ferroptosis, while the KDM2B-mediated ubiquitination pathway is responsible for changes in OGT levels. These findings are crucial for target selection and biomarker identification in stroke treatment.